Use of Herb Combination (Jamu Atoke) Before Mating to Improve Rat Pup Health - Andriyanto Andriyanto; Leliana Nugrahaning Widi; Hamdika Yendri; Kharisma Mardathilah; Diky Yuliansah; Firda Agustin; Aulia Andi Mustika; Wasmen Manalu (Majalah Kedokteran Bandung, 2022)
Mortality and health disturbances in children often correlate with maternal health and fertility. Avocado, mung bean sprouts, and holy basil have been traditionally used to improve maternal health, before and during pregnancy. This study was aimed to assess the efficacy of herbal combination of avocado, mung bean sprouts, and holy basil (Jamu ATOKE) in optimizing reproductive health. Eighteen female Sprague Dawley rats (9–10 weeks old, BW: 180–250 g) were randomly divided into 3 treatment groups (n=6 rats for each group) of control, group I and II. ATOKE were added into rats drinking water and consumed for 30 days before pregnancy. After the rats were pregnant and gave birth, pup per parent ratio, pup mortality, and pup health performance (body weight gain, feed and drink consumption, motor activity, pup speed in finding light and feed, red blood cell (RBC) count, white blood cell (WBC) count and differential, SGPT, SGOT, blood urea nitrogen (BUN), creatinine, and proinflammatory mediators (TNF-α and IL-6) were analyzed. Pups born to in group I had a generally better health performance compared to the control group. There was a 100% mortality in the litter of group II due to the excessive aggressive behavior of the dams as a sign of toxicity. Administration of 2.5% Jamu ATOKE showed the best effects on the health and intelligence of the rat pup.